Flavin mimetics: Synthesis and photophysical properties. (26th February 2021) - Răsădean, Dora-M.; Machida, Takashi; Sada, Kazuki; Pudney, Christopher R.; Pantoș, G. Dan
Abstract: We report the synthesis of new isoalloxazines using a microwave-assisted approach to make N -substituted-2-nitroanilines followed by one-pot reduction and condensation via Hemmerich's method. The influence of substituents on positions 7, 8, and 10 of flavin core on the optical properties is investigated. The aliphatic functionalities on N10 give rise to quantum yields of 0.7, while aromatic side-chains quench fluorescence. Relaxed geometries (DFT) of chiral and achiral derivatives have been used for TD-DFT calculations, which yielded good agreement with the experimental UV and CD data. Graphical abstract: Image 1